The Structure and Semantics of Al-Idhafah in Safinatu al-Shalah by Imam Abdullah bin Umar al-Hadrami: A Syntactic-Semantic Study - Supriyadi, Moh.; Rauf, Abdur (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2025)
The grammatical construction known as Al-Idhafah (annexation/genitive construction) refers to a syntactic relationship between two nouns, where the second noun (the mudhaf ilayh) defines or restricts the first noun (the mudhaf). However, idafah is not merely a combination of two nouns; it often carries implicit prepositional meanings, such as possession (of), origin (from), or association (about), making it essential for accurate sentence interpretation. Misunderstanding this structure may lead to errors in speaking, reading, and writing. This study explores how idafah is used and what meanings it conveys in the classical Islamic text Safinatu al-Shalah (